2010
DOI: 10.1080/17467586.2010.531748
|View full text |Cite
|
Sign up to set email alerts
|

Belief systems and action inferences as a source of violence in the name of Islam

Abstract: I draw on the belief system literature and use a cognitive mapping methodology to compare Islamists from the nonviolent Muslim Brotherhood and from the formerly violent groups al-Jihad and al-Jama'a al-Islamiyya in Egypt. Using data from in-depth interviews conducted in Egypt, I identify seven combinations of beliefs antecedent to decisions for and against violence and make three main claims. First, decisions for or against violence towards the state are only made if an individual believes that the state is vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Perceptions of injustice or humiliation create a third area of psychological vulnerability (Brown & Abernethy, ). Social scientists have long recognized perceived injustice and humiliation as central factors in understanding violence generally (van den Bos, ) and terrorism specifically (Deutsch, ; Dornschneider, ; Jurgensmeyer, 2000; Pargament, Magyar, Benore, & Mahoney, ). In the mid‐1970s, Hacker () concluded that “remediable injustice is the basic motivation for terrorism”.…”
Section: Psychological Vulnerabilitiesmentioning
confidence: 99%
“…Perceptions of injustice or humiliation create a third area of psychological vulnerability (Brown & Abernethy, ). Social scientists have long recognized perceived injustice and humiliation as central factors in understanding violence generally (van den Bos, ) and terrorism specifically (Deutsch, ; Dornschneider, ; Jurgensmeyer, 2000; Pargament, Magyar, Benore, & Mahoney, ). In the mid‐1970s, Hacker () concluded that “remediable injustice is the basic motivation for terrorism”.…”
Section: Psychological Vulnerabilitiesmentioning
confidence: 99%
“…State violence is associated with negative effects, including dampening (Davenport 2015; Lichbach 1987; Moore 1998; Zhukov and Talibova 2018) and pre-empting (Beiser-McGrath 2019; Danneman and Ritter 2014; De Jaegher and Hoyer 2019; Dragu and Przeworski 2019; Regan and Henderson 2002; Ritter and Conrad 2016; Sullivan 2016), as well as positive spurring (Dornschneider 2010; Finkel 2015; Francisco 2004) or ‘vengeance’ effects (Jaeger and Siddique 2018). Positive effects have been related to low or medium levels of state violence targeting early stage protest, whereas dampening effects have been related to increasing state violence against continued protest (Bell and Murdie 2018; Gurr 1970; Lichbach 1987; Lichbach and Gurr 1981; Muller and Weede 1990).…”
Section: State Violence Protest Space Curfews and Social Mediamentioning
confidence: 99%
“…Rather, studies have fallen into two main categories. First, various acts of violence are linked with their perpetrators' Muslim faith (Chapman, 2017;Dornschneider, 2010;Spruyt & Elchardus, 2012;Steven Fish et al, 2010;Venkatraman, 2007). Following Venkatraman (2007), discussion of Muslims' involvement in terrorism and conflict have produced heated academic debate.…”
Section: Introductionmentioning
confidence: 99%